Eco-friendly Methods of Natural Dye Extraction from Bark of Ficus religiosa and Their Impacts on Dyeing Technology in Nepal - Pandey, Durga Prasad; Parajuli, Numkant; Devkota, Anil; Aryal, Sangam; Bhandari, Netra Lal (NUTA Journal, 2020)
Plant-based natural dyes are eco-friendly and less allergic to the human body. Different reports on toxicity and allergic reactions that appeared in synthetic dyes cause interest in natural dyes in recent years. The present study focused on the feasibility of aqueous extraction of plant dyes from the bark of Ficus religiosa (Peepal), a historical tree of Hindu culture. Extracted dyes were characterized by ultra-violet visible (UV-Vis) spectroscopy and Fourier transform infrared (FTIR) spectroscopy to reveal the structural and functional confirmation of extracted dye. Dye was used for dyeing fabric using both natural and commercial mordant. Mordants such as lemon juice and metallic salts such as potassium dichromate (K2Cr2O7), copper sulphate (CuSO4.5H2O), and iron sulphate (FeSO4) are used to set extracted dye on cotton fabrics and other fibers. This research aims to find the effectiveness and feasibility study of the use of natural mordant instead of metallic mordant. The use of natural dyeing with natural mordant is very effective for health purpose but found to be expensive.